THE PROJECT-BASED LEARNING FOR GEOMETRY DURING THE COVID-19 PANDEMIC - Pratiwi Dwi Warih Sitaresmi; Imro Atus Soliha; Siti Nurazizah (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
The changing system in the current learning process at all levels of education due to the coronavirus pandemic. This study aimed to conduct literature review on project-based online learning during the Covid-19 pandemic and the impact on policies toward home learning activities. A project-based online learning system offers many ways to access learning materials for teachers and students. Many online learning platforms and media can be accessed for free. Some of the free platforms that have proven effective for managing online learning include Google Classroom and Edmodo. At least 12 free online learning resource applications can be used during the Covid-19 pandemic, including Rumah Belajar, ICANDO, Meja Kita, Indonesia X, Kelas Pintar, Google for Education, Microsoft Office 365, Quipper, Ruang Guru, Zenius, Sekolahmu, and Cisco Webex. Some obstacles in implementing online learning include limitations of the Internet and unfamiliar knowledge of teachers and students about the application of online learning media. Therefore, more effort is needed to address these issues, starting with individuals, families, educational institutions, providers, and government services.